1996
DOI: 10.1037/0022-3514.70.1.41
|View full text |Cite
|
Sign up to set email alerts
|

The role of interior design elements in human responses to crowding.

Abstract: The role or interior design elements in mitigating the negative relationship between residential crowding and psychological health was investigated. Residents of crowded homes with greater architectural depth-the number of spaces one must pass through to get from one room in the house to another-are less likely to socially withdraw or to be psychologically distressed than residents in crowded homes with relatively low depth. Additional analyses suggest that greater depth buffers the association between residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
102
1
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(113 citation statements)
references
References 29 publications
7
102
1
3
Order By: Relevance
“…95,96 The size, location, and permeability of interior rooms influence the degree of social control afforded to residents. 97,98 Territoriality, the ability to monitor and regulate use of space, is related to the physical environment. Tall, large structures, long interior corridors, lack of small group spaces, and poor visual surveillance capability (e.g., inability to monitor entrances, places for concealment) interfere with territorial control and feelings of ownership, and are associated with both actual crime levels and fear of crime.…”
Section: Personal Controlmentioning
confidence: 99%
“…95,96 The size, location, and permeability of interior rooms influence the degree of social control afforded to residents. 97,98 Territoriality, the ability to monitor and regulate use of space, is related to the physical environment. Tall, large structures, long interior corridors, lack of small group spaces, and poor visual surveillance capability (e.g., inability to monitor entrances, places for concealment) interfere with territorial control and feelings of ownership, and are associated with both actual crime levels and fear of crime.…”
Section: Personal Controlmentioning
confidence: 99%
“…Males have more need for personal space when ceiling height is low (Cochran, Urbanczyk 1982). People desire more space in a narrow room, and persons exhibit more personal space in corners than in the centre of a room, and maintain a closer distance when standing than while seated (Evans et al 1996).…”
Section: Caves and Bodiesmentioning
confidence: 99%
“…Finally, research from several domains has shown that the physical structure of living environments (e.g., dormitories) has a significant impact on the frequency and quality of social interactions (Baum & Davis, 1980;Evans, Lepore, & Schroeder, 1996).…”
Section: Lonelinessmentioning
confidence: 99%